An Energy Storage System for the Alto Douro Wind Power Plant: A Technical Study - Magalhães, Alexandre (2024)
Renewable energies are crucial to meeting global demand for environmentally friendly energy at a time when fossil fuels are being cut back. In recent years, and essentially due to the reduced reserves of fossil fuels, Portugal has been promoting investment in renewable energies as a way of freeing itself from energy imports and dependence on fossil fuels. However, despite the high number of hours of sunshine per day and the use of wind and hydraulic energy, production is unstable due to climate variability. All this climate instability translates into fluctuations in the energy released to the grid. In order to minimize this problem, energy storage systems have become a key element in guaranteeing the stability of the renewable energy supply at times of low production. This article presents a feasibility analysis of a renewable energy storage system with the aim of maximizing the profitability of a wind farm located in Portugal's Alto Douro region. As a starting point, a demand analysis is presented, as well as simulations of the system's performance in terms of energy use and profitability as a function of efficiency and power. Taking these assumptions and the analysis into account, a modular lithium battery storage system with high efficiency and fast charging and discharging powers was chosen.